Protective Effects of Hibiscetin on Ethanol-Induced Ulcers in Rats through Inhibition of Prostaglandin Synthesis/ Oxidative Stress/Caspase-3 and 9 Pathways - Alotaibi, Faisal (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim/Background: Ethanol (EtOH)-induced gastric ulcers are a prevalent gastrointestinal disorder characterized by severe inflammation, oxidative stress, and apoptotic cell death. This study aimed to investigate the potential protective effects of hibiscetin against EtOH-induced ulcers in rats. Materials and Methods: Rats were randomly divided into five groups: Normal control (normal saline), EtOH (1.5 mL), hibiscetin 10 mg/kg + EtOH, hibiscetin 20 mg/kg + EtOH, and hibiscetin 20 mg/kg alone (control). Ulcer index, pH, gastric juice, pro-inflammatory cytokines i.e., Interleukin-6 (IL-6), IL-1β, Tumor Necrosis Factor-alpha (TNF-α), and Prostaglandin E-2 (PGE2), oxidative stress-Malondialdehyde (MDA), antioxidant enzymes-Catalase (CAT), Superoxide Dismutase (SOD), reduced Glutathione (GSH), oxidative enzyme-Myeloperoxidase (MPO), apoptosis markers-caspase-3 and caspase-9 were estimated. Results: Both doses of hibiscetin administration significantly ameliorated EtOH-induced ulceration, as evidenced by reduced ulcer areas and preserved mucosal architecture. Furthermore, hibiscetin treatment downregulated IL-6, IL-1β, TNF-α, and PGE2 synthesis, which correlated with attenuated inflammation. Hibiscetin also exhibited robust antioxidant potential, as indicated by decreased MDA levels and increased CAT, SOD, and GSH activities. Moreover, hibiscetin suppressed MPO activity, indicating reduced neutrophil infiltration. Caspase-3 and caspase-9 activation demonstrated apoptotic cell death in the gastric mucosa which was restored by hibiscetin. Conclusion: The findings suggested that hibiscetin has gastroprotective activity against EtOH-induced ulcers and this might be related to its positive influence on oxidative stress, inflammatory response, and apoptotic pathways. Further research is warranted to explore its full clinical potential and safety profile.
Keywords: Antioxidant enzymes; Ethanol; Hibiscetin; Ulcer; Pro-inflammatory cytokines